2014
DOI: 10.1007/s11010-014-2018-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic efficacy of a novel dinuclear platinum(II) complex used with anti-MUC1 in human breast cancer cells

Abstract: Mucin 1 (MUC1) is overexpressed in various cancer cells especially in breast cancer cells. There are known research works on the use of anti-MUC1 antibody with docetaxel in ovarian cancer, but there are no data about combined therapy platinum compounds with anti-MUC1 in breast cancer. The aim of the study was to evaluate the antiproliferative properties of a new dinuclear platinum(II) complex (Pt12) used with anti-MUC1 in human breast cancer cells. The dinuclear platinum(II) complex (Pt12) has been synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In addition, the anti-MUC1 antibody GP1.4 decreased proliferation and migration of pancreatic cells by facilitating MUC1 internalization and inhibiting EGFR signaling 45 . The combined treatment with anti-MUC1 antibody GP1.4 and platinum (II) complex induced better cytotoxic and proapoptotic effects in breast cancer cell line 35 , 46 . A MUC1 antibody, C595, in association with docetaxel, significantly decreased tumor growth in a xenograft model of ovarian cancer by augmenting apoptosis and necrosis 47 .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the anti-MUC1 antibody GP1.4 decreased proliferation and migration of pancreatic cells by facilitating MUC1 internalization and inhibiting EGFR signaling 45 . The combined treatment with anti-MUC1 antibody GP1.4 and platinum (II) complex induced better cytotoxic and proapoptotic effects in breast cancer cell line 35 , 46 . A MUC1 antibody, C595, in association with docetaxel, significantly decreased tumor growth in a xenograft model of ovarian cancer by augmenting apoptosis and necrosis 47 .…”
Section: Discussionmentioning
confidence: 95%
“…In our latest studies we also proved that combination treatment with chemotherapeutic agents plus monoclonal antibody against MUC1 resulted in higher cytotoxicity and better proapoptotic effect than monotherapy [ 46 , 47 ], thus suggesting that combination strategy results in better efficacy than the use of chemotherapeutics alone.…”
Section: Discussionmentioning
confidence: 98%
“…Our preliminary studies showed that Pt 2 (4-ethylpyridine) 4 (berenil) 2 (Pt12) used together with anti-MUC1 antibody is more cytotoxic than Pt12 alone or cisplatin with anti-MUC1 in breast cancer MCF-7 and MDA-MB-231 cells. The anti-proliferative effect of Pt12 with anti-MUC1 was dependent on the estrogen receptor status of the breast cancer cells [ 20 ]. Pt12 with anti-MUC1 was proved to be a stronger inhibitor of collagen biosynthesis in breast cancer cells compared to Pt12 alone and cisplatin with anti-MUC1.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA’s kits were purchased from Uscn Life Science Inc. and BioVendor. The chemical synthesis and structure of Pt12 was presented in publication [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation